FORENSIC RADIOLOGY AND IMAGING FOR VETERINARY RADIOLOGISTS. Issue 3 (24th February 2017) - Watson, Elizabeth; Heng, Hock Gan
Abstract : Imaging studies are often of evidentiary value in medicolegal investigations involving animals and the role of the veterinary radiologist is to interpret those images for courts as an expert or opinion witness. With progressing interest in prosecuting animal crimes and strengthening of penalties for crimes against animals, the participation of veterinary radiologists in medicolegal investigations is expected to increase. Veterinary radiologists who are aware of radiographic and imaging signs that result in animal suffering, abuse, or neglect; knowledgeable in ways radiology and imaging may support cause of death determinations; conversant in postmortem imaging; comfortable discussing mechanisms and timing of blunt or sharp force and projectile trauma in imaging; and prepared to identify mimics of abuse can assist court participants in understanding imaging evidence. The goal of this commentary review is to familiarize veterinary radiologists with the forensic radiology and imaging literature and with the advantages and disadvantages of various imaging modalities utilized in forensic investigations. Another goal is to provide background information for future research studies in veterinary forensic radiology and imaging.